Identification of Information Technology Potential as an Attraction of Betawi Museum, Setu Babakan - Mularsari, Ardi; Nugraha, Rizki Nurul; Saleh, Muhammad Surya (West Science Business and Management, 2024)
In the current era of information technology development, it cannot be ignored that this innovation has changed people's lifestyle to become modern. The utilization of information technology also helps make it easier to work smoothly in various industries, one of which is the tourism industry. The purpose of this study is to identify the types of information technology applied by Museum Betawi to increase their attractiveness, analyze the sustainability strategies carried outby Museum Betawi in the application of information technology, and provide recommendations for Museum Betawi to improve the effectiveness of strategies and the use of information technology to strengthen as one of the destinations of interest to tourists. The research method used was qualitative, namely direct observation and interviews with the Betawi Museum manager. The analysis technique used is descriptive qualitative. The results of our research, Museum Betawi located in Zone A Setu Babakan is one of the tourist destinations that utilizes information technology as a tourist attraction. The museum applies 3 (three) information technologies, namely digital platforms consisting of websites, Google Forms, and social media; two-dimensional technology, namely QR Codes; andelectronic devices, namely Projectors and Touchscreen TVs called interactive projection rides. The potential of the application of information technology can provide an interactive experience for tourists, assist in the management of tourist destination resources, and as a destination promotion. Museum Betawi's current sustainability strategy is to focus on maintaining existing information technology. The challenges of Museum Betawi in the application of information technology are information inaccuracies, damage to technological devices and promotional strategies.